THE ROLE OF MOTHER TONGUE AND THAT OF CONTRASTIVE ANALYSIS IN COMMUNICATIVE LANGUAGE TEACHING - Ahmad Yani (Journal of Education Papua Baru, 2022)
The teaching of a second/foreign language has been aimed at encouraging learners to use the target language they are learning in real communication. The objectives of this paper are to explore the roles of mother tongue and that of contrastive analysis in communicative language teaching. Method used in this study is a library research. The findings of the study suggest that using mother tongue helps beginner learners to cope with communication problem, while contrastive analysis helps teachers in choosing topic, in explaining different notions between second  language and mother tongue, and  helps explaining different notions found in both target language and mother tongue.Keywords: mother tongue, contrastive analysis, communicative                        language teaching